Pengembangan Model Pembelajaran Berbasis Project Untuk Meningkatkan Kecakapan Hidup (Life Skill) Pada Mata Pelajaran IPS di SMP Kota Tegal - Anis Khamidah Khamidah; Suriswo Suriswo; Dewi Apriani (Universitas Pancasakti Tegal, 2025)
Project-based learning model (PBL) as one of the innovative learning models based on students (student center) can be used and selected by teachers as one of the alternative learning methods that will provide a new